Through the Nigerian Prism: An Appraisal of Constitutional Democracy and Acts of Terrorism - Adedayo, Ayoade M (Journal of Malaysian and Comparative Law, 2014)
Terrorism, increasingly, is becoming part and parcel of the Nigerian experience. This is highly unfortunate in a country with considerable social, economic and religious tensions. Acts of terrorism seemingly threatens emerging democracy in the country. While the confrontation between acts of terrorism and democratic norms or traditions are not unique in the global experience, Nigeria as an emergent power in Africa is threatened as a nation, with dire consequences for the West Africa sub-region. Home grown terror groups such as Boko Haram have set up a confrontation with the Nigerian state that undermines the Constitution and democracy which emphasized dialogue, debate and consensus. It is difficult for such rationality to co-exist with acts of terror perpetrated in the name of religion. Thus this paper seeks to describe and illuminate the Nigerian terrorism experience and challenges through the spectrum of constitutional democracy. It warns that this regional giant cannot win the fight against acts of terror through a response that is not in accordance with constitutional democracy.